Efficacy and safety of edoxaban for treatment of portal vein thrombosis following danaparoid sodium in patients with liver cirrhosis. Issue 1 (27th April 2017) - Nagaoki, Yuko; Aikata, Hiroshi; Daijyo, Kana; Teraoka, Yuji; Shinohara, Fumi; Nakamura, Yuki; Hatooka, Masahiro; Morio, Kei; Nakahara, Takashi; Kawaoka, Tomokazu; Tsuge, Masataka; Hiramatsu, Akira; et al.
Abstract : Aim: To compare the efficacy and safety of edoxaban and warfarin for treatment of portal vein thrombosis (PVT) following danaparoid sodium in patients with liver cirrhosis. Methods: Fifty cirrhotic patients with PVT treated initially for 2 weeks with danaparoid sodium were enrolled in this retrospective cohort study. Treatment was later switched to either edoxaban ( n = 20) or warfarin ( n = 30). We compared the efficacy and safety of edoxaban and warfarin for up to 6 months. The PVT volume was measured by dynamic computed tomography before treatment, at 2 weeks, and at 1, 3, and 6 months. Results: There were no significant differences in the clinical characteristics of patients in the two groups. Treatment with edoxaban reduced the volume of PVT from 1.42 cm 3 at 2 weeks to 0.42 cm 3 at 6 months, and prevented exacerbation of PVT at 6 months after treatment with danaparoid sodium ( P = 0.016). In contrast, treatment with warfarin resulted in increased PVT volume from 1.73 cm 3 at 2 weeks to 2.85 cm 3 at 6 months, despite the control of the international normalized ratio in 57% of the patients ( P = 0.005). Multivariate regression analysis identified edoxaban therapy as the single significant and independent determinant of PVT reduction at 6 months ( P = 0.0014, hazard ratio 6.400). Clinically significant gastrointestinal bleeding was encountered in 3 of 20 (15%) patients of the edoxaban group and 2 of 30 (7%) of the warfarin group ( P = 0.335). Conclusion: Edoxaban following danaparoid sodium is an effective anticoagulant and could be potentially considered as one of the treatment options for PVT in cirrhotic patients.